قاعدة"الرُّخص لا تناط بالمعاصي" دراسة تأصیلیَّة تطبیقیَّة - بوطیّب, خدیجة (University of Eloued-جامعة الوادي, 2016)
Our study, "The permission's rule does not include the sins", is within the Islamic Fiqh Madhabs. We started our study with an introduction which argues: to what extent can we apply the permission's rule when there is a sins?. We answered this question in three themes. An introductory which includes small summary about the Fiqh rules. And the first theme includes the definition of the permission rule and its origins. Also it includes a distinction between the sin and its causes and the scholars mathhabs in sin makers' permissions. The second theme deals with the application of this rule on some issues like: sweeping on the socks (during making the ablution), travelling to do sins, travelling for relaxing, and the abortion of adultery' son. In the end we gave some results that madhab Elshafia applied this rule, and the Hanabila, but the Hanafi Madhab did not permit this rule, where the Maliki Madhab has a controversy about it. The recommendations: interest in the study of such juristic rules that are closely linked to the life of the contemporary Muslim.
مذكرة ماستر
Keywords: الرُّخص/المعاصي/قاعدة; Permits/sins/bases